Gestational hypobaric hypoxia induces long-term biomechanical and structural alterations in the descending thoracic aorta - Garcia-Herrera, C; Urrutia-Aguilera, G (Elsevier Ltd, 2026)
Chronic exposure to hypobaric hypoxia (HH) during gestation, typical of high-altitude environments (≥2500 m), is known to affect fetal development; however, its long-term vascular consequences remain poorly understood. This study evaluated the biomechanical, functional, and morphostructural effects of gestational HH on the descending thoracic aorta (DTA) of adult guinea pigs. Pregnant animals were exposed to normoxia (group N) or HH (group H) during gestation, and offspring were maintained under normoxic conditions until one year of age. Mechanical behavior was characterized through tensile, ring-opening, and axial pre-stretching tests, while ex-vivo vasomotor function was assessed using wire myography and histological analysis. HH offspring showed increased material stiffness and residual strain, reduced axial physiological strain, diminished vasodilation, and enhanced vasoconstriction. Histology revealed thicker walls, larger luminal radii, elevated collagen and elastin content, and fewer endothelial cells compared to controls. These findings demonstrate that gestational HH induces persistent vascular remodeling, linking mechanical stiffening and endothelial dysfunction to a compensatory antihypertensive adaptation. © © 2026. Published by Elsevier Ltd.